Why We Need Womanist Ways: A Means of Liberation for Black Churchwomen - Thomas, Alexis Carter (Journal of feminist studies in religion, 2025)
Womanist theology is presented as counter to patriarchal hegemonic Black church culture. The author proposes that womanist theology provides liberating concepts and ways of being that have the power to reform and increase the well-being of Black churchwomen. The article discusses the 8-Week Womanist Workshop - a research study exploring how inviting Black churchwomen to engage with womanist theology may encourage new tools and practices that change their minds about the traditions and harms of patriarchal hegemonic Black church culture. Through examining womanist scholarship and practices of Black churches, the author argues that the former can repair the harms done by the latter. The article aims to encourage more church leaders to consider how cultivating spaces for womanist theological formation holds power to connect and liberate Black churchwomen.